Dissolution properties, solid-state transformation and polymorphic crystallization: Progesterone case study - Araya Sibaja, Andrea Mariela (2014)
Progesterone is a natural steroid hormone and a poor soluble drug which presents two polymorphs (forms 1 and 2). Different methods to obtain form 2 were tested and a complete solid-state characterization of both polymorphs (forms 1 and 2) was conducted. X-ray powder diffraction, hot stage microscopy, Fourier transform infrared, dispersive Raman, 13C solid-state nuclear magnetic resonance spectroscopy, thermal analysis, scanning electron microscopy techniques and intrinsic dissolution rates (IDR) were applied to investigate physical-chemical and dissolution properties of these two polymorphs. Form 2 was obtained from diluted solutions and from melting after cooling at room temperature. Form 1 was obtained from concentrated solutions and, a mixture of both polymorphs was crystallized from intermediate solutions. The crystal habit was not a distinctive characteristic of each polymorph. The effect of mechanical stress was evaluated in the metastable polymorph (form 2). We observed that grinding form 2 produced seeds of form 1 that induced the transformation of form 2 into form 1 at high temperature. The polymorphic quantification from XRD patterns of ground samples were carried out by the Rietveld method. After grinding and at room temperature conditions (∼25 °C), it was observed the transformation of 17% of form 2 into form 1 in 10 days.